Childhood lung function as a determinant of menopause-dependent lung function decline. (November 2021) - Triebner, Kai; Bui, Dinh; Walters, Eugene Haydn; Abramson, Michael J; Bowatte, Gayan; Campbell, Brittany; Dadvand, Payam; Erbas, Bircan; Johns, David P; Leynaert, Bénédicte; Lodge, Caroline J; Lowe, Adrian J; et al.
Highlights: Lung function declines especially rapidly in postmenopausal women who had poor lung function during childhood. Strategies to reduce respiratory morbidity are required. Strategies to reduce respiratory morbidity need to consider the whole lifespan. Abstract: Rationale: The naturally occurring age-dependent decline in lung function accelerates after menopause, likely due to the change of the endocrine balance. Although increasing evidence shows suboptimal lung health in early life can increase adult  susceptibility to insults, the potential effect of poor childhood lung function on menopause-dependent lung function decline has not yet been investigated. Objectives: To study whether menopause-dependent lung function decline, assessed as forced vital capacity (FVC) and forced expiratory volume in one second (FEV1), is determined by childhood lung function. Methods: The Tasmanian Longitudinal Health Study, a cohort born in 1961, underwent spirometry at age seven.  At ages 45 and 50 serum samples, spirometry and questionnaire data were collected ( N  = 506). We measured follicle stimulating and luteinizing hormones to determine menopausal status using latent profile analysis. The menopause-dependent lung function decline was investigated using linear mixed models, adjusted for anthropometrics, occupational level, smoking, asthma, asthma medication and study year, for the whole study population and stratified by tertiles of childhood lung function. Measurements and Main Results: The overall menopause-dependent lung function decline was 19.3 mL/y (95%CI 2.2 to 36.3) for FVC and 9.1 mL/y (-2.8 to 21.0) for FEV1. This was most pronounced (pinteraction=0.03) among women within the lowest tertile of childhood lung function [FVC 22.2 mL/y (1.1 to 43.4); FEV1 13.9 mL/y (-1.5 to 29.4)]. Conclusions: Lung function declines especially rapidly in postmenopausal women who had poor low lung function in childhood. This provides novel insights into respiratory health during reproductive aging and emphasizes the need for holistic public health strategies covering the whole lifespan.